2015
DOI: 10.1155/2015/295891
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pruritus in Chronic Liver Disease

Abstract: Background. There continues to be uncertainty on the ideal treatment of pruritus in chronic liver disease. The aim of this study was to gather the latest information on the evidence-based management of pruritus in chronic liver disease. Methodology. A literature search for pruritus in chronic liver disease was conducted using Pubmed and Embase database systems using the MeSH terms “pruritus,” “chronic liver disease,” “cholestatic liver disease,” and “treatment.” Results. The current understanding of the pathop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Support for this theory comes from the fact that application of bile acids to the skin causes itch 7 , 8 and one study has suggested that cholestatic pruritus is mediated by the bile acid-activated receptor, the G-protein-coupled receptor, TGR5, expressed by peptidergic neurons of mouse dorsal root ganglia and spinal cord 10 . It is well known that pruritus can be profoundly debilitating; orthotopic liver transplantation may be the only option for severe and intractable pruritus 11 . Further investigations are warranted into the causative mechanism and optimal treatment of cholestatic pruritus.…”
Section: Introductionmentioning
confidence: 99%
“…Support for this theory comes from the fact that application of bile acids to the skin causes itch 7 , 8 and one study has suggested that cholestatic pruritus is mediated by the bile acid-activated receptor, the G-protein-coupled receptor, TGR5, expressed by peptidergic neurons of mouse dorsal root ganglia and spinal cord 10 . It is well known that pruritus can be profoundly debilitating; orthotopic liver transplantation may be the only option for severe and intractable pruritus 11 . Further investigations are warranted into the causative mechanism and optimal treatment of cholestatic pruritus.…”
Section: Introductionmentioning
confidence: 99%
“…In our case, UDCA was not successful, and neither was the insertion of an NB tube. NB tubes have been used with success in severe cholestasis but mainly in the context of congenital aetiologies and in particular in those with low GGT cholestasis 17. Our patient had a low normal GGT level initially, a typical feature of congenital cholestasis, hence an NB tube insertion was attempted while the genetic results were pending.…”
Section: Discussionmentioning
confidence: 95%
“…Pruritus can be a severe, debilitating symptom of PBC, and can be exacerbated by treatment with OCA 19 20. If the pruritus is not well managed, treatment of PBC can be challenging; in some patients, pruritus can be an impediment to the effective use of OCA 22.…”
Section: Managing Pruritus In Patients With Pbcmentioning
confidence: 99%
“…Patients with PBC may be asymptomatic or present with a variety of symptoms, most commonly fatigue and/or pruritus 2 17. Pruritus, or itchy skin, affects up to 70% of patients with PBC and can interfere with daily life; because it is often worse at night, pruritus may prevent or disrupt sleep, increasing fatigue and affecting patient quality of life (QoL) 18–20. PBC-related pruritus often manifests in the limbs, causing itch on the palms and feet, as well as on the arms and legs 19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation